Initial experience with angioplasty of symptomatic M2 MCA atheromatous lesions. (4th June 2010) - Hussain, Muhammad Shazam; Cheng-Ching, Esteban; Bain, Mark; Spiotta, Alejandro M; Sivapatham, Thinesh; Hui, Ferdinand; Moskowitz, Shaye I; Gupta, Rishi
Abstract : Background and purpose: Symptomatic intracranial atherosclerosis has been associated with a high rate of recurrent stroke. The safety of treatment of more distal atheromatous lesions with angioplasty has not been systematically reported. Methods: We retrospectively reviewed our institutional database for all patients treated with intracranial angioplasty and stenting from January 2008 to July 2009. A total of 108 patients were treated and five patients were treated with angioplasty for a symptomatic M2 middle cerebral artery stenosis with fluctuating neurological examinations. We report our experience with these patients. Results: All five patients underwent technically successful treatment with a reduction of the stenosis to <50%. There were no periprocedural complications and all patients had cessation of their clinical fluctuations. Two patients were found to have symptomatic restenosis with one patient suffering a disabling stroke at 5 months and the second patient a transient ischemic attack at 4 months who was subsequently successfully re-treated with angioplasty and stent placement. Conclusions: Angioplasty of M2 MCA lesions is technically feasible in our cohort of neurologically unstable patients, but the durability of this treatment will require more extensive study.